Prolonged Release of Anti-inflammatory Diclofenac Sodium from In Situ Loaded Thermosensitive Chitosan Hydrogels for Localized Applications - Do, Nga Hoang Nguyen; Le, Ha Vu; Nguyen, Khoa Dang; Ha, Anh Cam (Indonesian Journal of Chemistry, 2025)
Previous work developed a thermosensitive hydrogel from chitosan (CS) and β-glycerophosphate (GP) loaded with diclofenac sodium (DIC) using a post-loading method. The hydrogel as a wound dressing exhibited burst release of DIC within 5 h, rendering it suitable for immediate anti-inflammatory treatment. For the first time, the in situ loading method has been applied to synthesize an injectable CS/GP hydrogel for prolonged DIC release. The optimal synthesis condition is at 1.0 w/v% CS (high molecular weight of 324 kDa) and 4.0 w/v% GP, yielding the hydrogel capable of sol-gel transition at 37 °C. The porous structure of the hydrogels is filled with DIC, ensuring efficient drug entrapment. The hydrogels demonstrate prolonged DIC release over 7 days, achieving a cumulative drug release (CDR) ranging from 62.39 to 80.51%. At an initial DIC loading of 3000 µg/mL, the hydrogel maintains a drug concentration above 10 µg/mL after 6 days of release. DIC release kinetics are temperature-dependent, with a higher CDR at 39 °C (simulating an inflammatory condition) than 37 °C (normal body temperature), and governed by drug diffusion and hydrogel network swelling. This study provides a novel approach for synthesizing an injectable temperature-responsive CS hydrogel for local anti-inflammatory DIC delivery.